2008
DOI: 10.2174/092986708785909148
|View full text |Cite
|
Sign up to set email alerts
|

On the Pathogenesis and Neuroprotective Treatment of Parkinson Disease: What have we Learned from the Genetic Forms of this Disease?

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder affecting nearly 3 million patients in Europe and North America, characterized by a core phenotype of motor deficits, akinesia, rigidity, postural disturbance and tremor, which is complicated by other neurological deficits during its long progression. Our knowledge about the pathophisiology of PD was limited, up to 25 years ago, to the observation of the lesion of the nigro-striatal dopamine neurons in these patients. The subjects who developed PD as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 145 publications
0
6
0
Order By: Relevance
“…Even so, the role played by neuroinflammation in PD is under intense debate (Gao et al, ; Marchetti & Abbracchio, ; McGeer & McGeer, ; Mena, Rodriguez‐Navarro, Ros, & de Yebenes, ; Niranjan, ; Tansey & Goldberg, ; Whitton, ). Accordingly, particular immunological responses in PD could be either detrimental or beneficial, with neurotoxic and neuroprotective mechanisms interacting in a delicate balance.…”
Section: Is There a Link Between Neuroinflammation And Parkinson's DImentioning
confidence: 99%
“…Even so, the role played by neuroinflammation in PD is under intense debate (Gao et al, ; Marchetti & Abbracchio, ; McGeer & McGeer, ; Mena, Rodriguez‐Navarro, Ros, & de Yebenes, ; Niranjan, ; Tansey & Goldberg, ; Whitton, ). Accordingly, particular immunological responses in PD could be either detrimental or beneficial, with neurotoxic and neuroprotective mechanisms interacting in a delicate balance.…”
Section: Is There a Link Between Neuroinflammation And Parkinson's DImentioning
confidence: 99%
“…The special sensitivity of aged PK‐KO glia to oxidative stress while there is strong resistance in young PK‐KO cells, suggest that these cells are exposed to a greater oxidative challenge and that a compensatory GSH synthesis is increased for some time until it collapses with senescence and renders the cells more susceptible [16]. Furthermore, in the differential oxidative stress response between WT and PK‐KO cultures, parkin as an E3 ligase, which participates in the ubiquitin–proteasome system, protein aggregation and protein posttranslational modifications, may play a very important role [40–43].…”
Section: Resultsmentioning
confidence: 99%
“…PARKIN gene mutations are the most frequent cause of autosomal recessive Parkinson's disease in the populations from all over the world. Till date a wide variety of mutations in the PARKIN gene have been detected, including exon deletions and duplications, as well as point mutation (Klein et al 2005;Madegowda et al 2005;Biswas et al 2006;Abbas et al 1999;Chaudhary et al 2006;Mena et al 2008). A most recent study has identified a deletion hot spot between exons 2 and 5.…”
Section: Discussionmentioning
confidence: 99%